Middle East Oil Pricing Systems in Flux - Bassam Fattouh; Ahmed Mehdi; Owain Johnson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2021)
This issue of the Oxford Energy Forum is devoted to analysing the recent shifts in oil trade flows and the major developments in pricing benchmarks in Middle East crude and products markets. The region is experiencing a series of dramatic structural changes that are transforming crude and products flows, as well as leading to an increased focus on the price benchmarks used to underpin activity in the region. The Gulf countries traditionally exported crude oil, while also importing much of the refined products that they required. The construction of several major refineries around the Gulf has changed this model, turning the region into an exporter of refined products. This new focus on refined products in part reflects the increased domestic demand within the region, as local populations grow and as energy-intensive industries develop. Meanwhile, the impact of the COVID-19 pandemic on energy demand has weighed particularly heavily on the Gulf as one of the world's major suppliers of hydrocarbons, exposing some of the cracks in existing oil benchmarks, oil price assessment processes, and the relationship between the different benchmarks. The pressures on governments and the region's national oil companies to ensure they are maximizing their revenues from their crude oil and products exports is leading to a new focus on the trading activity and pricing mechanisms that underpin the Gulf's exports, with recent months seeing some major changes-such as ADNOC removing destination restrictions on its crude grades and moving from a retroactive to a forward-pricing model. With the launch of the ICE Futures Abu Dhabi (IFAD), the region now has two exchanges (IFAD and the Dubai Mercantile Exchange (DME)) and two crude oil futures contracts, while the incumbent benchmark (Platts Dubai) continues to attract liquidity and remains dominant in pricing crude going out of the region. And the COVID-19 demand shock gave Shanghai International Energy Exchange (INE) oil futures contracts a boost, as excess supply of oil naturally gravitated to China, the biggest oil importing country in the world, increasing spot activity in delivered barrels into the country. As Middle East-Asia crude and products trade flows become more important over time, and as the role of Asia as the most important demand centre consolidates further, the role of Asian players in pricing crude and products will only increase and the desire to turn regional benchmarks into global ones will only intensify. But as trade flows between the Middle East and Asia consolidate, the nature of the relationship will continue to evolve, with consequences on the pricing of crude and products. While Asia will remain the main importer of Middle East crude, refiners in the Middle East and Asia will increasingly compete on products markets and petrochemicals, as both have very ambitious plans to expand refining capacity and integrate refining assets with petrochemicals.
Keywords: 330